The Al-Talaqqi Learning Model in Enhancing Understanding of Arab Turats Books and its Analysis in the Mutammimah al-Jurumiyah Book at Madrasah Aliyah Mu'allimat NW Anjani Academic Year 2023-2024 - Jannah, Miftahul; Fahrurrozi, Fahrurrozi; Sauqani, Syamsu; Hajras, Multazam (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This study investigates the efficacy of the Al-talaqqi learning model in improving comprehension of Arab Turats books, specifically through the analysis of Mutammimah Al-Jurumiyah at Madrasah Aliyah Mu'allimat NW Anjani during the academic year 2023-2024. The background emphasizes the significance of traditional Arabic grammar texts in Islamic education and the challenges students face in comprehending them. The research employs a qualitative approach, utilizing document analysis as the primary method of data collection. Data is gathered from students' interpretations and insights derived from their engagement with Mutammimah Aljurumiyah using the Al-talaqqi model. Analysis involves thematic coding and interpretation to extract meaningful patterns and insights. Findings indicate that the Al-talaqqi model significantly enhances students' understanding and application of Arabic grammar concepts. Consequently, the study concludes that integrating the Al-talaqqi model into Islamic education curriculum can foster a deeper grasp of Arabic grammar among students. This research suggests implications for curriculum development, highlighting the importance of pedagogical innovations in enhancing educational outcomes in Arabic language studies.